2021
DOI: 10.1002/jgc4.1466
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from a pilot genetic counseling intervention using motivational interviewing and the extended parallel process model to increase cascade cholesterol screening

Abstract: Familial hypercholesterolemia (FH) is an inherited condition resulting in increased risk of premature cardiovascular disease. This risk can be reduced with early diagnosis and treatment, but it can be challenging to identify individuals with FH. Cascade screening, the most efficient and cost‐effective identification method, requires FH patients to communicate with their at‐risk family and encourage them to pursue screening. Beyond FH, patients with conditions increasing disease risk to family members report ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The two positive probands gave 4 relatives information and subsequently underwent genetic testing with two having positive results [49]. Motivational interviewing and the extended parallel process model with probands has been tested as an intervention to improve cascade screening and found on average 2.23 new relatives were contacted and 2.46 were screened [50]. A feasibility study based on core principles from the Dutch model, found that when the FH Foundation served as the agency to directly engage with 11 FH probands, they were able to engage nine relatives [51].…”
Section: Resultsmentioning
confidence: 99%
“…The two positive probands gave 4 relatives information and subsequently underwent genetic testing with two having positive results [49]. Motivational interviewing and the extended parallel process model with probands has been tested as an intervention to improve cascade screening and found on average 2.23 new relatives were contacted and 2.46 were screened [50]. A feasibility study based on core principles from the Dutch model, found that when the FH Foundation served as the agency to directly engage with 11 FH probands, they were able to engage nine relatives [51].…”
Section: Resultsmentioning
confidence: 99%
“…Second, communications from clinicians applying these recommendations from individuals and families with FH should be tested in prospective trials. A recent pilot intervention incorporating motivational interviewing and the EPPM in genetic counseling with parents of a child with FH demonstrated increased disclosure and cascade testing rates among at-risk relatives [ 44 ]. Findings from the current study complement this pilot genetic counseling intervention by providing examples of message features future interventions can incorporate to communicate about FH risk and motivate cascade testing uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Post‐intervention surveys for this study included the modified RBD scale, the Informing Relatives Inventory, and information on risk communication and screening of relatives. Detailed analysis of the pre‐ and post‐intervention survey data was done in a separate CHEERS analysis (Baldry et al., 2021).…”
Section: Methodsmentioning
confidence: 99%